MODERN APPROACHES TO TEACHING RUSSIAN AS A FOREIGN LANGUAGE: DIGITAL TRANSFORMATION AND COMMUNICATIVE FOCUS (Web of Teachers: Inderscience Research, 2026)
This article examines modern approaches to teaching Russian as a foreign language (RFL), which have evolved in the context of the digital transformation of education and a changing student population. Key trends in the development of RFL teaching methods are analyzed: adaptive learning using digital platforms, a multimodal approach, case studies, group interaction technologies, and the strengthening of the axiological component. Particular attention is paid to the cognitive characteristics of Generation Z, which is characterized by clip-based thinking and a need for visualization and interactivity. The need to integrate traditional and innovative methods to develop sustainable communicative competence in international students is substantiated.